Evidence of independent glycerol electrooxidation behavior on different ordered domains of polycrystalline Pt - Fernández, Pablo S. (2015)
We investigate the electrooxidation of glycerol (GlOH) on polycrystalline Pt. The results obtained in the presence of GlOH were compared with those of fresh and disturbed low-index Pt single crystals [(111), (100) and (110)]. Monitoring of the oxidation currents of GlOH by cyclic voltammetry on the different surfaces revealed that the electrooxidation of GlOH is highly sensitive to the order of the polycrystalline Pt atoms. Interestingly, after being disturbed by the application of voltammetric cycles, the combined responses of the disordered single crystals become similar to that of polycrystalline Pt. The changes in the current values associated with the specific potentials at which each oxidation peak takes place suggest that different ordered domains of Pt oxidize GlOH independently. This simple approach can clearly assist in our understanding of the effect of the order of surface atoms in a given reaction, not only in electrochemical reactions.